Production of liquid fish protein (LFP) using modified methods of fermentation - Daquiado, Divina Gracia Alba (Iloilo College of Fisheries and Ocean Sciences, 2005)
Elevation of fermenting temperatures and increasing inoculum addition served as studied parameters in the fermentation process. Small shrimps (Acetes sp.) or locally known as alarming was used as substrate. Three levels of fermenting temperatures and inoculum addition were employed resulting to nine fermenting lots. The samples were swirled (clockwise) five times, twice a day (1 in the morning and 1 in the afternoon) and were withdrawn in duplicates every another day for 10 days. The liquid fish protein (LFP) recovered was analyzed for pH, total soluble proteins (TSP) and percent hydrolysate yields. Post fermentation analyses include the general monitoring of the appearance and odor of the hydrolysates. The pH of the fermenting substrate and inoculum recovered during the sample withdrawals were assumed to be the same. The increase of pH values from 7-8.3 showed that the fish hydrolysates are basic in nature. This is due to the production of ammonia by the hydrolysis of proteins and other components. The results suggest that in all fermenting temperatures with inoculum addition the pH exhibited increase/decrease as fermentation progresses. The final pH values may be affected by the products of hydrolysis of the different components as fermentation progresses. However, the pH range is still above 7. Statistically, in the production of TSP, it has been observed that, if inoculum is not used, the fermentation could be continued until the 10th day. Based on the experimental results with fermenting temperature and addition of inoculum as parameters, it is best not to use inoculum to attain a protein rich product. Generally, the individual factors are significantly different. In the hydrolysate yields, the results are
Thesis (Undergraduate, Bachelor of Science in Fisheries) College of Fisheries and Ocean Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Liquid Fish Protein; Fermentation